1992
DOI: 10.1523/jneurosci.12-06-02177.1992
|View full text |Cite
|
Sign up to set email alerts
|

SAG: a Schwann cell membrane glycoprotein

Abstract: We report on characterization of a 170,000 Da glycoprotein found exclusively in the PNS. We refer to this protein as the Schwann cell membrane glycoprotein (SAG). SAG contains the HNK-1 carbohydrate, which is considered by some to be a marker of adhesion molecules. Its N-terminal sequence is not similar to previously known polypeptide sequences. SAG is found exclusively in the PNS, is present in rat sciatic nerve prior to myelination, and is in both myelinating and nonmyelinating Schwann cells. Tumors of Schwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…In addition to these abundant glycoproteins, the PNS myelin holds three other, very minor glycoproteins: Schwann cell membrane glycoprotein (SAG), found exclusively in PNS myelin, associated with Schwann cells (Dieperink et al, ); Schwann cell myelin protein (SMP), expressed in vivo exclusively by myelinating and nonmyelinating Schwann cells and oligodendrocytes (Dulac and Le Douarin, ; Dulac et al, ); and the oligodendrocyte‐myelin glycoprotein (OMgp), involved in the formation and maintenance of the myelin sheaths (Kottis et al, ; Vourc'h and Andres, ).…”
Section: Myelin Glycoproteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to these abundant glycoproteins, the PNS myelin holds three other, very minor glycoproteins: Schwann cell membrane glycoprotein (SAG), found exclusively in PNS myelin, associated with Schwann cells (Dieperink et al, ); Schwann cell myelin protein (SMP), expressed in vivo exclusively by myelinating and nonmyelinating Schwann cells and oligodendrocytes (Dulac and Le Douarin, ; Dulac et al, ); and the oligodendrocyte‐myelin glycoprotein (OMgp), involved in the formation and maintenance of the myelin sheaths (Kottis et al, ; Vourc'h and Andres, ).…”
Section: Myelin Glycoproteinsmentioning
confidence: 99%
“…SAG is found in PNS and plays a role in myelination and stability of the myelin membrane. Bovine SAG contains HNK‐1 epitope, but rat SAG does not (Dieperink et al, ).…”
Section: Myelin Glycoproteinsmentioning
confidence: 99%
“…Since antibodies to the glycolipid galactocerebroside very efficiently block myelin formation by Schwann cells in vitro (Ranscht et al 1987), this molecule may be another likely candidate involved in the compensation for MAG or N-CAM. Other cell surface components of Schwann cells which might compensate for MAG or N-CAM are L1 (Wood et al 1990), Ecadherin (Fannon et al 1995), the Schwann cell membrane glycoprotein SAG (Dieperink et al 1992), the Schwann cell component P30 (Daston and Ratner 1991), the myelin and lymphocyte protein rMAL (SchaerenWiemers et al 1995) and plasmolipin (Gillen et al 1996). In conclusion, the formation of normal myelin in double mutants deficient in both MAG and N-CAM does not strictly argue against a compensatory role for N-CAM in the absence of MAG, but may reflect a high degree of flexibility in molecular compensation of the Schwann cell during myelin formation.…”
Section: Peripheral Nerve Myelin Is Normally Formed In the Absence Ofmentioning
confidence: 99%
“…Several of these glycoproteins have been shown to be cell-adhesion molecules, such as N-CAM, L1, Ng-CAM, Nr-CAM, TAG-1, MAG, and others (10 -14). Based on these observations, the HNK-1 reactive carbohydrate has now been considered to be a marker of cell adhesion molecules in the nervous system (15). Previous studies have suggested that HNK-1 carbohydrate is involved in the organization of early neuronal settling and axonal outgrowth patterns (7, 16 -18).…”
mentioning
confidence: 99%